(untitled) (Academicia Globe: Inderscience Research, 2026)
The article develops a methodological approach to assessing the economic efficiency of fruit and vegetable clusters based on economic-mathematical modeling. A system of efficiency indicators is proposed, including production, financial, and export parameters. An econometric model is developed to quantitatively evaluate the impact of key factors on cluster performance. The obtained results can be used in the development of strategies for the agricultural sector and the digitalization of agriculture.